Pengaruh Intensitas Pameran dan Jumlah Surveyor terhadap Volume Penjualan Studi Kasus PT. Mega Central Finance Cabang Cibinong - Marpaung, Annaria Magdalena; Hasibuan, David H.M.; Aryono, Agus (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
In achieving required selling target, company can raise cooperation with dealer of Yamaha, Honda, and Suzuki to bring about exhibition. PT. Mega Auto Finance is company operating in financing of Yamaha, Honda, and Suzuki motorcycle. By increasing exhibition intensity and sum of account officer, it can increase selling as high as 23 + 25 = 48 in breakdown as follows: Y= (94) + (23) (1) + 25 (1) = 94 + 23 + 25 = 142 The result of processing of double linear correlation data, itâs yielded r = 0,876, it means there is significant and positive influence between exhibition intensity and sum of account officer toward selling result. Coefficient determination (CD) = 0,7674; it means exhibition intensity and sum of account officer/surveyor have contribution toward selling result as high as 76,74%, The rest as high as 23,26% is influenced by other factor. At real hypothesis test of 0,05, it is found F-count (29,69) > F-tabel (4,96). Therefore, Ho is rejected and Ha is accepted. It can be conclude there is correlation between exhibition intensity and sum of account officer/surveyor with selling result. Keywords: Marketing management, Exhibition;